2016
DOI: 10.1177/1758834016659791
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in a patient with glioblastoma on antipsychotic therapy for schizophrenia: a case report and literature review

Abstract: Glioblastoma is not only the most common primary brain tumor, but also the most aggressive. Currently, the most effective treatment of surgery, chemotherapy and radiation therapy allows for a modest median survival of 15 months. Here, we report a case of a 57-year-old male with histologically confirmed glioblastoma with unfavorable prognostic characteristics (poor performance status and persistent neurological symptoms after surgery), whose expected 5-year survival is 0%. Further genetic analysis offered a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Within a histologic grade, IV astrocytoma cohorts, akin to lower-grade astrocytomas, a mutation in IDH1 or IDH2 carries the most significant prognostic value [ 4 , 7 ] ( Table 3 ). IDH-mutant GBMs show a median survival of 24–31 months (depending on treatment modalities) in comparison to 9–15 months for their histologically similar wildtype counterparts [ 4 , 7 , 106 , 108 ], although there are reports of much longer survival in some of these cases [ 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. These tumors also occur at a younger age than their IDH-wildtype GBM counterparts (5 th decade compared to 7 th decade, respectively) [ 34 , 52 , 105 , 106 ], and have increased rates of TP53 and ATRX mutation as well as lower rates of TERT p mutation, PTEN mutation, and EGFR amplification [ 107 ].…”
Section: Idh-mutant Glioblastomamentioning
confidence: 99%
“…Within a histologic grade, IV astrocytoma cohorts, akin to lower-grade astrocytomas, a mutation in IDH1 or IDH2 carries the most significant prognostic value [ 4 , 7 ] ( Table 3 ). IDH-mutant GBMs show a median survival of 24–31 months (depending on treatment modalities) in comparison to 9–15 months for their histologically similar wildtype counterparts [ 4 , 7 , 106 , 108 ], although there are reports of much longer survival in some of these cases [ 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. These tumors also occur at a younger age than their IDH-wildtype GBM counterparts (5 th decade compared to 7 th decade, respectively) [ 34 , 52 , 105 , 106 ], and have increased rates of TP53 and ATRX mutation as well as lower rates of TERT p mutation, PTEN mutation, and EGFR amplification [ 107 ].…”
Section: Idh-mutant Glioblastomamentioning
confidence: 99%
“…Furthermore, several reports show that CPZ can inhibit cancer cell growth through several mechanisms (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In addition, epidemiological data suggest a reduction of cancer risk in psychiatric patients treated with CPZ or related antipsychotic compounds (16,17), and anecdotal reports of favorable GBM evolution in psychiatric patients treated with neuroleptic medications have been published (16,18).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity in most cases remains unclear with less than 3%‐5% of the survival rate after 5 years. Without treatments, most patients can only survive for about 3 months 50,51 . Malaka et al reported that in newly diagnosed glioblastoma patients, the use of anti‐angiogenic therapies did not significantly improve overall survival, 52 indicating that new treatments and drugs are necessary to overcome this issue.…”
Section: Discussionmentioning
confidence: 99%